Development of voice-based smart home security system using Google voice kit - Gunawan, Teddy Surya; Mokhtar, Muhammad Najib; Kartiwi, Mira; Ismail, Nanang; Effendi, Mufid Ridlo; Qodim, Husnul (IEEE, 2020)
Nowadays, speaker verification and speech recognition to control the smart home system has gained popularity. This paper presents the design and implementation of the voice-based smart home security system using Google Voice Kit, Raspberry Pi 3, relay, and magnetic lock. There are two methods implemented in this research, i.e., Cloud Speech and Assistant methods. Three experiments were conducted, including response time to the voice command, multiuser experiment, and multi-environment experiment. Results showed that the Cloud Speech method performs better than the Assistant method in processing time and accuracy. The Cloud Speech method requires less than 1.67 ms to lock and unlock the magnetic lock. The accuracy of the multiuser experiment using the Cloud Speech method is 90% on average. Finally, on the various environmental condition, the Cloud Speech method has an accuracy of 95%, 90%, and 95% for the ambient room, cocktail noise, and loud musical noise, respectively.